Wolny dostęp do wiedzy : otwarte zasoby naukowe i edukacyjne w społeczeństwie opartym na wiedzy - Janowska, Anna A. (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2016)
Open on-line access to culture, knowledge and educational resources is an approach that allows different social and economic actors to profit in many ways, such as by reducing inequalities caused by access fees for scientific and educational materials, faster introduction of new solutions, creating possibilities of interdisciplinary projects uniting different participants. It is also an impulse of change in scientific and educational publishing.